ALPHABETIC LETTER RECOGNITION APP FOR AUTISTIC STUDENT LEARNING USING FLASH MULTIMEDIA ON HOMESHCOOLING - M.Rizki Khadafi; Melva Sari Panjaitan; Zulham Sitorus (Sean Institute, 2022)
This study discusses how to teach children who have special abilities with the application of Macromedia Flash 8, Adobe Audition 1.5, Adobe Photoshop CS3 with the Software Development Life Cycle (SDLC) method by displaying Audio Visual. This study aims to assist in the learning process for autistic children so that they can recognize letters by utilizing computer technology. That way, autistic children can learn and recognize letters like normal children in general and can develop their talents